ENTREPRENEURIAL SPIRIT AS A STRATEGY FOR MSME SUSTAINABILITY IN COMMUNITY SERVICE ACTIVITIES - Erza, Osni; Indriyarti, Eko Retno; Razman, Eljannati Eros; Rizkia, Annisa Ayu; Anggraeni, Dewi (Universitas Bunda Mulia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are pivotal to the national economy; yet, the sustainability of community-based micro-enterprises encounters numerous problems, especially concerning the entrepreneurial capabilities of business proprietors. An essential internal factor for MSME sustainability is the entrepreneurial spirit, which includes innovativeness, proactiveness, and the readiness to identify and seize business possibilities. This community service initiative seeks to assess and enhance the entrepreneurial spirit of MSME participants as a basis for bolstering business sustainability. The initiative was executed in partnership with the Lapak Puri Kartika MSME community in Ciledug, Tangerang, employing an instructional and participatory methodology. The applied methods consisted of direct presentations and interactive question-and-answer sessions, supplemented with a one-group pre-test and post-test evaluation design. The implementation phases included initial communication with community partners, needs assessment, internal team planning, delivery of training materials, activity execution, and feedback evaluation. Assessment tools were employed to evaluate participants' comprehension of entrepreneurial spirit principles and their opinions of the activity's advantages. The findings demonstrate an enhancement in participants' comprehension and recognition of the significance of entrepreneurial spirit in the management and sustainability of MSME operations. Participants exhibited heightened motivation and preparedness to embrace more innovative and adaptive actions in addressing business difficulties. Moreover, the activity was regarded as offering tangible advantages for prospective business growth. This community service effort demonstrates that enhancing and assessing entrepreneurial spirit via an educational-participatory approach is a pertinent and effective technique for promoting MSME sustainability at the community level. This initiative aims to provide a foundational paradigm for sustainable community service initiatives that emphasize the enhancement of MSME entrepreneurial capability.